SYNTHESIS OF NOVEL PET AND FLUORESCENT PROBES FOR THE MOLECULAR IMAGING OF RHEUMATOID ARTHRITIS AND CANCER - Al-Karmi, Salma (My University, 2016)
This thesis describes novel molecular imaging strategies that can ultimately be used for imaging rheumatoid arthritis (RA) and cancer. In the first approach, a convenient method for the preparation of a “turn on” near-infrared (NIR) optical reactive oxygen species (ROS) probe and its 18F analogue is described. The probe and its radiolabeling precursor are prepared in high yield (82 and 98% respectively) via a Suzuki coupling in two steps. Chemical induction studies revealed the probe selectively responds to hydroxyl and superoxide radicals. The PET probe was accessed via a late-stage fluorination approach from a nitropyridine precursor in a 62% decay-corrected radiochemical yield. As a proof of concept, the PET probe was assessed in vivo in C57BL/6 mice using a doxorubicin induced model of cardiac ROS which revealed a statistically significant retention in the heart as compared to untreated mice (p ˂ 0.05). The probe additionally demonstrated high-blood retention in vivo, which is likely due to albumin binding. Less hydrophobic derivatives of this probe were synthesized in a similar approach with the ultimate goal of improving in vivo clearance. Building on this work, the synthesis of a meso fluorinated cyanine dye derived from copper-catalyzed halogen exchange of IR780 iodide is discussed. Optimized reaction conditions led to a 68% yield in the presence of a phosphaadamantane ligand and a copper (II) catalyst. The fluorinated probe exhibited enhanced fluorescence in comparison to IR780 in solution. The corresponding ROS probes (hydrocyanines) were assessed in a PC-3 cell assay where the fluorinated probe exhibited 2-3 fold fluorescence enhancement. Radiolabeling to produce the 18F analogue was attempted, but this was found to be irreproducible. This fluorinated dye along with IR780 and other synthesized fluorescent probes were encapsulated in F-127 micelles which resulted in the preparation of monodispersed micelles (PDI ≤ 0.2). Improved solubility and fluorescence were observed as compared with unencapsulated dyes. An MTT assay performed on the encapsulated ROS probe revealed it was considerably less cytotoxic than the parent probe. Alternatively, a targeted approach via the development of molecular probes based on two classes of high affinity TACE enzyme inhibitors is described. Three compounds were synthesized and assessed in a fluorogenic assay in which one compound demonstrated binding in the micromolar range (IC50 = 1770 nM) while the remaining compounds demonstrated low nanomolar affinity (IC50 = 5-10 nM). Intermediates that could serve as precursors in 18F labeling via a prosthetic group labeling strategy were prepared.